2003
DOI: 10.1046/j.1445-2197.2003.t01-2-02654.x
|View full text |Cite
|
Sign up to set email alerts
|

Single stage primary anastomosis without colonic lavage for left-sided colonic obstruction due to acute sigmoid volvulus: a prospective study of one hundred and ninety-seven cases

Abstract: Primary colonic anastomosis can be safely done for obstructed left colon due to acute sigmoid volvulus without intraoperative colonic lavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 0 publications
4
42
0
Order By: Relevance
“…De et al [26] reported 197 patients who had a single stage primary anastomosis without colonic lavage for leftsided colonic obstruction due to acute sigmoid volvulus; only 2 (1.01%) patients developed symptomatic anastomotic leak. In a similar prospective study by Raveenthiran [29] , 57 consecutive patients with acute sigmoid volvulus had emergency RPA without ontable lavage or caecostomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De et al [26] reported 197 patients who had a single stage primary anastomosis without colonic lavage for leftsided colonic obstruction due to acute sigmoid volvulus; only 2 (1.01%) patients developed symptomatic anastomotic leak. In a similar prospective study by Raveenthiran [29] , 57 consecutive patients with acute sigmoid volvulus had emergency RPA without ontable lavage or caecostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, obstruction of the left colon is managed by a multi-stage defunctioning colostomy and resection. However, there is a growing acceptance of one-stage primary resection and anastomosis with the use of on-table antegrade irrigation [24,[26][27][28] . However, several studies have suggested that on-table lavage may not be necessary for a safe emergency RPA of unprepared left colon [26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leakage of anastomosis is caused by many factors [27,28]. Anastomoses made in urgent cases of trauma [29], cancer with obstruction [30], diverticulum of the colon [16,31], twisting [32] and peritonitis [33] have also shown that absolute cleanness of bowel before forming anastomosis is not necessary. The wall of inflated intestine after the removal of occlusion remains resilient enough, and anastomosis is mechanically hermetic.…”
Section: Discussionmentioning
confidence: 99%
“…Sigmoid volvulus has been treated successfully by resection and primary anastomosis without colonic lavage. 7 We have approached our left-sided obstructed patients in a similar manner arguing that, provided mobilisation and blood supply are good, a side-to-side stapled colorectal anastomosis will deal with any size disparity in the bowel and allow a rapid decompression of the system. Our experience is presented.…”
mentioning
confidence: 99%